2017
DOI: 10.1097/md.0000000000006743
|View full text |Cite
|
Sign up to set email alerts
|

Glycated hemoglobin level is an independent predictor of major adverse cardiac events after nonfatal acute myocardial infarction in nondiabetic patients

Abstract: The effect of glycemic control on the prognosis of nondiabetic patients after acute myocardial infarction (AMI) remains uncertain. We investigated whether glycated hemoglobin (HbA1c) is associated with adverse outcomes after AMI in nondiabetic patients. In this observational study, we enrolled nondiabetic patients with AMI in the emergency department of 2 medical centers from January 2011 to September 2014. All patients received primary percutaneous coronary intervention and were divided into 4 groups accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The two comparative studies are in accordance with this study and prove the theory that dyslipidemia and hypertension are risk factors for ACS. 13 The mean BMI in the group of subjects with ACS was 25.3 ± 2.7, significantly higher (p=0.006) than the mean BMI of the non ACS subject group (23.7 ± 2.3). The study conducted by Hartopo et al, (2016) with ACS subjects had mean BMI of 23.9 ± 3.2, it is almost the same as this study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The two comparative studies are in accordance with this study and prove the theory that dyslipidemia and hypertension are risk factors for ACS. 13 The mean BMI in the group of subjects with ACS was 25.3 ± 2.7, significantly higher (p=0.006) than the mean BMI of the non ACS subject group (23.7 ± 2.3). The study conducted by Hartopo et al, (2016) with ACS subjects had mean BMI of 23.9 ± 3.2, it is almost the same as this study.…”
Section: Discussionmentioning
confidence: 78%
“…9 This study and the comparative research prove the theory that high BMI reflects the metabolic syndrome which is a risk factor for ACS. 10 HbA1c levels in the ACS group were higher (8.2) than in the non ACS group (7.7), but not significant (p=0.106).The study conducted by Chen et al, (2017) showed that the mean HbA1c levels in the CHD group were significantly higher than not CHD (5.91 ± 0.34 and 5.77 ± 0.36 with p = 0.012). 13 In this study it was found that the incidence of STEMI was higher, where the inferior STEMI (47.4%; 18 patients) was more than the anterior STEMI (28.9%; 11 patients), anteroseptal (13.2%; 5 patients) and NSTEMI (10.5%; 5 patients).The study conducted by Merza et al, (2016) stated that from the sample of 68 people, there were 40 STEMI samples.…”
Section: Discussionmentioning
confidence: 86%
“…Degradation of the glycocalyx alters endothelial barrier permeability and may thus cause damage to the microcirculation, which contributes to organ dysfunction [29][30][31]. Another study showed that HbA1c was a signi cant predictor of major adverse cardiac events after acute myocardial infarction (AMI) in nondiabetic patients [32]. Glycemic control may contribute to the damage to vascular structures caused by a poor glycemic status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, poor glycemic control can lead to an increased formation of advanced glycation end products, which can cause severe vascular damage [33]. Therefore, HbA1c, which re ects metabolic control and embedded ongoing vascular injury or atherosclerosis, can be considered a reliable indicator of adverse outcomes in nondiabetic populations after AMI [32]. It should be noted that glucose level variability was greater in patients with high HbA1c than in those with normal HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of any large studies in South Africa that examined the prevalence and predictive value of admission blood glucose in patients presenting with AMI and our study may provide important epidemiological insight into elevated admission blood glucose as a risk factor for MACE. Although HbA1c, which reflects metabolic and glycaemic control, has been shown to be a significant predictor of MACE after AMI, (25) elevated admission blood glucose may serve as a cost-effective and easily obtainable alternate prognostic marker.…”
Section: Discussionmentioning
confidence: 99%